LKS Asam Basa Berbasis Pendekatan Ilmiah dalam Meningkatkan KPS Berdasarkan Kognitif Siswa - Istiqomah Istiqomah; Ila Rosilawati; Nina Kadaritna (Jurnal Pendidikan dan Pembelajaran Kimia, 2017)
This research aimed to describe the effectiveness of scientific approach based student worksheets in improving science process skills (SPS) insight from students cognitive. The method of this research was quasi experimental with 2x2 factorial design. The population of this research was all students of XI IPA SMAN 15 Bandarlampung on 2016/2017. The sample were XI IPA-4 and the XI IPA 2 which taken by purposive sampling. The data of this study were analyzed by using two ways ANOVA test and t test. The result of this research was no interaction between learning with scientific approach based worksheets and cognitive on SPS; learning process using student worksheets scientific approach was effective to improve SPS; SPS high and low cognitive ability with learning using worksheets Scientific Approach wass higher than conventional worksheets; SPS high cognitive ability was higher than low cognitive ability with learning using worksheets scientific approach.Penelitian ini bertujuan mendeskripsikan efektivitas LKS pendekatan ilmiah dalam meningkatkan KPS berdasarkan kognitif siswa. Metode penelitian menggunakan kuasi eksperimen dengan desain faktorial 2x2. Populasi penelitian seluruh siswa kelas XI IPA di SMAN 15 Bandarlampung tahun 2016/2017. Sampel penelitian ini kelas XI IPA 4 dan kelas XI IPA 2 yang diambil dengan teknik purposive sampling. Data penelitian dianalisis menggunakan uji two ways ANOVA dan uji t. Hasil penelitian menunjukan tidak terdapat interaksi antara pembelajaran menggunakan LKS terhadap KPS berdasarkan kemampuan kognitif, pembelajaran menggunakan LKS pendekatan ilmiah efektif untuk meningkatkan KPS, KPS siswa kognitif tinggi dan rendah dengan pembelajaran menggunakan LKS pendekatan ilmiah lebih tinggi dibandingkan LKS konvensional, KPS siswa kognitif tinggi lebih tinggi dibandingkan KPS siswa kognitif rendah menggunakan LKS pendekatan ilmiah.Kata kunci: LKS, Pendekatan ilmiah, KPS, kemampuan kognitif